1997
DOI: 10.1007/bf01373425
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic activity of 3,6-dibenzyl-2,5-dioxopiperazine, cyclo(L-Phe-L-Phe)

Abstract: Summary.After oral administration, dipeptide Phe-Phe-OMe 1 exhibits anthelmintic activity against Echinococcus multilocularis larvae, cestoda, in mongolian gerbils (intraperitoneal localization), but not against Hymenolepis nana, cestoda, in fasted mice (gastro-intestinal localization). This compound rapidly provides its cyclization product dioxopiperazine 2 in pH 7.4 buffer at 37°C, but was stable at pH 2.4 during 16h at 30°C. It was postulated that dipeptide 1 could act as a prodrug of 2. Initial pharmacokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Cyclo( l -Phe– l -Phe) ( 357 ) originally isolated from Penicillium nigricans was also isolated from a marine mangrove endophytic fungus [ 171 ], and exhibited good anthelmintic activity against Hymenolepis nata and Schistosoma mansoni in mice [ 172 ].…”
Section: Non-tryptophan–non-proline Cyclodipeptidesmentioning
confidence: 99%
“…Cyclo( l -Phe– l -Phe) ( 357 ) originally isolated from Penicillium nigricans was also isolated from a marine mangrove endophytic fungus [ 171 ], and exhibited good anthelmintic activity against Hymenolepis nata and Schistosoma mansoni in mice [ 172 ].…”
Section: Non-tryptophan–non-proline Cyclodipeptidesmentioning
confidence: 99%
“…Cyclo( L -Phe- L -Phe) is of special interest among DKPs in foods and beverages because it is found not only in chicken essence [11] but also in some commercial chicken soups such as bouillon cubes and powders. Besides its known biological activities (antifungal [31] and anthelmintic activities [32]), we have now shown that cyclo( L -Phe- L -Phe) is a dual inhibitor of the SERT and ACh that has both antidepression and antiamnesic effects in animal models. Animal studies have demonstrated that post-training SSRI administration improves memory more than that of pre-training administration [33].…”
Section: Discussionmentioning
confidence: 99%
“…Drimentines have anthelmintic activity against various parasites [253][254][255]. DKPs demonstrate an antimalarial effect [256][257][258][259].…”
Section: Anthelmintic Activitymentioning
confidence: 99%